Three-dimensional particle-in-cell plasma simulation on Intel Xeon Phi: performance optimization and case study - Meyerov, I.B.; Bastrakov, S.I.; Surmin, I.A.; Gonoskov, A.A.; Efimenko, E.S.; Bashinov, A.V.; Korzhimanov, A.V.; Larin, A.V.; Muraviev, A.A.; Rozanov, A.I.; Savichev, M.R. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2015)
An efficient application of computational systems equipped with Intel Xeon Phi coprocessors for the laser-plasma simulation is considered. The features of Xeon Phi architecture that influence the performance of Particle-in-Cell plasma simulation are analyzed. The PICADOR parallel plasma simulation code previously optimized for Xeon Phi is described. Its performance on Xeon Phi compared to CPU is studied on three computationally intensive plasma simulation problems. The ratio of computational time on Xeon Phi to CPU is discussed for the main stages of the Particle-in-Cell method. It is shown that, depending on the features of a physical problem, the use of Xeon Phi can be both advantageous and disadvantageous compared to CPU.